Differences by Sex, Ear, and Sexual Orientation in the Time Intervals between Successive Peaks in Auditory Evoked Potentials - McFadden, Dennis (2010)
Auditory-evoked-potential (AEP) data from two studies originally designed for other purposes were reanalyzed. The auditory brainstem response (ABR), middle-latency response (MLR), and long-latency response (LLR) were measured. The latencies to each of several peaks were measured for each subject for each ear of click presentation, and the time intervals between successive peaks were calculated. Of interest were differences in interpeak intervals between the sexes, between people of differing sexual orientations, and between the two ears of stimulation. Most of the differences obtained were small. The largest sex differences were for interval I → V in the ABR and interval N1 → N2 of the LLR (effect sizes > 0.6). The largest differences between heterosexuals and nonheterosexuals were for the latency to Wave I in both sexes, for the interval Na→ Nb in females, and for intervals V → Na and Nb → N1 in males (effect sizes > 0.3). The largest difference for ear stimulated was for interval N1 → N2 in heterosexual females (effect size ~0.5). No substantial differences were found in the AEP intervals between women using, and not using, oral contraceptives. Left/right correlations for the interpeak intervals were mostly between about 0.4 and 0.6. Correlations between the ipsilateral intervals were small; i.e., interval length early in the AEP series was not highly predictive of interval length later in the series. Interpeak intervals appear generally less informative than raw latencies about differences by sex and by sexual orientation.